Avaliação da viabilidade técnica de dispositivos de baixo custo para automação de um sistema hidropônico NFT - Baron, Luiz Carlos (2019)
Hydroponic systems require frequent adjustments in nutrient solution and variations in watering shifts due to illuminance, temperature, and air humidity. These activities result in the employment of labor or high costs of automated hydroponic systems. This work aimed at the elaboration and analysis of the technical and operational feasibility of the low-cost modular automation for a small scale NFT hydroponic system. The system performs closed-loop control of electrical conductivity, open-loop control of the nutrient solution flow so that the time of the driven pump depends on the intensity of illumi-nance, temperature and humidity of the air. The system also performs the verification of pump failures, profile dampening and power failure, presenting reliability in emer-gency battery power when there is a lack of mains power. The control of the electrical conductivity has proved feasible, however the sensor presents a decalibration that can be corrected by programming. On the other hand, the pH control was impracticable due to the great variation presented by the meter when continuously submerged in the nutritive solution. The system has a consumption of 7.548 W, which represents for one day 181.15 W.h.day-1, with an energy cost of R$ 4.18 per month considering the cur-rent tariff of 0.769 R$.kW-1.h-1. The system automation presented a relatively low cost for the basic configuration, with R$ 657.90 for one bench and R$ 1,076.90 for ten benches and for the intermediate configuration of R$ 859.63 and R$ 2,292.23 respec-tively. Only for an isolated system powered by photovoltaic module and with battery backup the system presented a relatively high cost of R$ 2,183.03 and R$ 7,458.73 for one and ten benches, respectively.